Principles of Security and Trust First International Conference, POST 2012, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2012, Tallinn, Estonia, March 24 - April 1, 2012, Proceedings - Degano, Pierpaolo; Guttman, Joshua D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the first International Conference on Principles of Security and Trust, POST 2012, held in Tallinn, Estonia, in March/April 2012, as part of ETAPS 2012, the European Joint Conferences on Theory and Practice of Software. The 20 papers, presented together with the abstract of an invited talk and a joint-ETAPS paper, were selected from a total of 67 submissions. Topics covered by the papers include: foundations of security, authentication, confidentiality, privacy and anonymity, authorization and trust, network security, protocols for security, language-based security, and quantitative security properties.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Systems and Data Security; Computers and Society; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity